Characterization of failure modes and shear behavior of reinforced concrete beams without stirrups based on combined non-destructive testing - Shengtao Li; Xudong Chen; Joan R. Casas; Yangyang Sun (Developments in the Built Environment)
The shear capacity of concrete beams without stirrups exhibits high variability, and the specific causes behind this difference in capacity remain unclear. This study conducts a combined analysis of shear failure using various advanced non-destructive testing (NDT) methods. Digital Image Correlation (DIC) observed crack propagation, Distributed Fiber Optic Sensing (DFOS) detected strain in longitudinal reinforcement, and Acoustic Emission (AE) analyzed internal damage during critical crack development. The results indicate that identical beams without stirrups exhibit two failure modes with high and low load-bearing capacities, leading to a difference in capacity exceeding 65 %. The beams exhibit significant differences in stress states during the formation of critical shear cracks, as indicated by the strain profile measured through DFOS. Combined NDT methods successfully revealed that variations in crack propagation paths and differential crack coalescence are key factors leading to differences in shear capacity. This helps to elucidate the structural state changes during the failure process of the beams without stirrups.